Methicillin-resistant Staphylococcus pneumonia and underlying asymptomatic sarcoidosis: Are they related? A post-mortem case report - Sirohi Deepika; Sengupta P; Kumar Harsh (Wolters Kluwer Medknow Publications, 2010)
Staphylococcus aureus is a rare cause of pneumonia, though in recent times methicillin-resistant strains are emerging increasingly as causative pathogens. Methicillin resistant Staphylococcus aureus (MRSA) has been reported to cause rapidly fatal hemorrhagic pneumonia. Most of these strains have been found to produce a lethal exotoxin called Panton-Valentine leukocidin. The finding of an underlying asymptomatic multisystem sarcoidosis was unusual in the case being reported here.